Effects of soybean meal source and level on growth performance of weanling pigs - Lawrence, K.R.; Hastad, C.W.; Hanni, S.M.; Young, M.G.; Webster, M.J.; Barker, M.R.; James, B.W.; Groesbeck, C.N.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; et al. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 525 weanling pigs (initially 13.0 lb) were used in two experiments to evaluate the effects of soybean meal source and level on growth performance of early weaned pigs. In both experiments, dietary treatments included a control diet containing no soybean meal, or diets containing 20% or 40% of either solvent extracted soybean meal (SBM) or extruded-expelled soybean meal (EESoy). In Exp. 1, diets were formulated with NRC (1998) nutrient values for the solvent extracted soybean meal and previously determined values (1998 KSU Swine Day Report of Progress) for the extruded-expelled soybean meal. In Exp. 1, from d 0 to 7, increasing solvent extracted soybean meal or extrudedexpelled soybean meal decreased (linear, P<0.05) ADG. Feed efficiency was reduced with an increase of either soybean meal source (SBM quadratic, P<0.05; EESoy linear, P<0.05). However, the mean ADG and F/G of pigs fed solvent extracted soybean meal were better than the mean of pigs fed extruded- expelled soybean meal. No differences were found in growth performance from d 7 to 14 and 14 to 21. However, from d 0 to 14, F/G became poorer (linear, P<0.06) as either soybean meal source increased, and the mean F/G of pigs fed solvent extracted soybean meal was better than those fed extrudedexpelled soybean meal. For the overall growth period, d 0 to 21, F/G became poorer (linear, P<0.04) as solvent extracted soybean meal increased. After the trial was completed, the soybean meal sources were chemically analyzed and the extruded-expelled soybean meal was found to be lower in crude protein (43.6% vs 46.5%) than what was used in diet formulation. We speculated that the differences in growth performance between the two soybean meal sources could have been a result of the low protein (lysine) concentrations. Therefore, in Exp. 2 diets were formulated with actual analyzed nutrient soybean meal values. In Exp. 2, from d 0 to 7, increasing either soybean meal source resulted in decreased (linear, P<0.01) ADG and ADFI, and reduced (quadratic, P<0.04) F/G. The mean ADG, ADFI, and F/G of pigs fed solvent extracted soybean meal were better than the mean of those fed extruded-expelled soybean meal. From d 7 to 14, ADG and F/G improved (linear, P<0.05) with increasing solvent extracted soybean meal. Increasing extruded-expelled soybean meal had no affect on ADG or F/G but decreased (linear, P<0.03) ADFI. From d 0 to 14, increasing solvent extracted soybean meal decreased (linear, P<0.02) ADFI. Increasing extruded-expelled soybean meal decreased ADG, ADFI, and decreased F/G (linear, P<0.01). The mean ADG, ADFI, and F/G of pigs fed solvent extracted soybean meal was better than the mean of pigs fed extrudedexpelled soybean meal. For the overall trial, increasing extruded-expelled soybean meal decreased ADG and ADFI (linear, P<0.01) and the mean ADG and ADFI, were less than those fed solvent extracted soybean meal. Because of previous research demonstrating equal or better growth performance of pigs fed extruded-expelled soybean meal, the results of these trials led us to suspect that poor quality extruded-expelled soybean meal was used in this trial. At the conclusion of the study, soybean meal sources from both trials were analyzed for trypsin inhibitor. Results of the trypsin inhibitor assay suggest that the extruded-expelled soybean meal from both experiments was underprocessed, resulting in poor growth performance. In conclusion, trypsin inhibitor values are extremely important in verifying quality of extruded-expelled soybean meal.
Keywords: Soybean meal; Weanling pigs; Swine